Communication and Transition of Self-Identity of Ex-Prostituted Women to Residents of Rehabilitation Institutions - Syaiful Rohim (Jurnal Ilmu Komunikasi, 2021)
The arrest and the process of guidance rehabilitation activities for ex-prostitution make them and their identities become different before undergoing the arrest and guidance process. These are that maybe felt by all ex-prostitution in rehabilitation. The purpose of this study was to explore the phenomenon of communication in the rehabilitation program as well as the changes of identity and self of ex-prostitution after experiencing an arrest by the law enforcement officers or Civil service police Unit (Satpol PP) and the rehabilitation program in rehab place. This research method was using qualitative approach as an analysis in this research activities, by tracing the changes in self-concept or psychological changing and consciousness which is experienced by an Ex-prostitute womenafter being caught in a “raid” operation and put into a rehabilitation center. The results of this study reveal that ex-prostitutes or other nicknames that they usually called slut before being caught, had a concept and awareness of themselves as someone who has a typology of work as Professional, Semi-Professional and Amateur prostitutes according to their background and their reasons for choosing to be prostitutes. After the arresting and guidance in the rehabilitation center, make the subject reformulate his physical, psychological and social existence as a new identity, including physical appearance, attitude and social orientation. This research gives contribution in the form of recommendations for policy-making and the process of guidance for ex-prostitutes, so it can make easier communication and the effectiveness of guidance because it sees from the aspect of awareness and identity as objects and subjects in the rehabilitation process.